2014
DOI: 10.1097/nen.0000000000000032
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term High-Level Exercise Promotes Muscle Reinnervation With Age

Abstract: The histologic features of aging muscle suggest that denervation contributes to atrophy, that immobility accelerates the process, and that routine exercise may protect against loss of motor units and muscle tissue. Here, we compared muscle biopsies from sedentary and physically active seniors and found that seniors with a long history of high-level recreational activity up to the time of muscle biopsy had 1) lower loss of muscle strength versus young men (32% loss in physically active vs 51% loss in sedentary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
162
4
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 150 publications
(182 citation statements)
references
References 50 publications
11
162
4
5
Order By: Relevance
“…As a result, the size of each motor unit increases with age [68]. As neural innervation changes with aging, muscle fiber types that are generally dispersed in the muscle in younger adults tend to group together in older inactive adults [57,69], reflecting reduced reinnervation. Also, older muscle fibers tend to be angulated in shape, reflecting denervation of muscle fibers [69].…”
Section: Skeletal Muscular Changes Associated With Agingmentioning
confidence: 98%
“…As a result, the size of each motor unit increases with age [68]. As neural innervation changes with aging, muscle fiber types that are generally dispersed in the muscle in younger adults tend to group together in older inactive adults [57,69], reflecting reduced reinnervation. Also, older muscle fibers tend to be angulated in shape, reflecting denervation of muscle fibers [69].…”
Section: Skeletal Muscular Changes Associated With Agingmentioning
confidence: 98%
“…28 An expanding list of studies are indicating that the application of FES on healthy muscle can elicit some of the same metabolic benefits as voluntary muscle active exercise. [29][30][31] The purpose of this study was to confirm that FES is an effective and safe means to reduce chronic muscle spasms in the top line of horses. The present study will add objective histological evidence to previous clinical findings, 27 through the evaluation of equine epaxial muscle biopsies harvested before and after 8 weeks of FES treatments.…”
Section: Functional Electrical Stimulation (Fes) Has Beenmentioning
confidence: 99%
“…For example, the frequency of mitochondria is higher in athletic than sedentary seniors, with mitochondria being even more positively affected than the excitation -contraction coupling apparatus. Zampieri et al (2015) have shown that the frequency of calcium release unit (CRU)-mitochondrial pairs is threefold higher in senior sportsmen; this functional coupling up-regulates ATP production when muscle is active (Brookes et al 2004;Shkryl and Shirokova 2006;Mosole et al 2014). Notably, there is also significant up-regulation of miR-206 expression in senior sportsmen, compared with young adults and healthy sedentary seniors; this microRNA has been shown to play a specific role in the early events of regeneration (Cacchiarelli et al 2010).…”
Section: Physical Activity As a Model For Interventions That Might Prmentioning
confidence: 91%